Evaluation of River Hydromorphology Using the Morphological Quality Index (MQI): A Case Study of the Megun–Fasham River Section - Ilanloo, Maryam (Revista Brasileira de Engenharia de Biossistemas, 2025)
Over the past two decades, riverbeds in mountainous areas have been manipulated by humans due to their tourist attractions. Today, river geomorphology has entered a new era and turns to the basis of studying environmental changes which are used to River canal management. So, studying the trend of hydromorphological of this river is very essential. The purpose of this study was to evaluate the hydromorphological conditions of a part of Jajrood River from Meghun to Fasham using MQI method. In this regard, the desired information was collected using field observations, remote sensing science and geographic information system. After preparing satellite images, the river was intercepted and divided into 7 sections using the MQI method. The first and second phases determined the quality of the intervals and the number of changes. The study results show that there have been many changes in the bed in this part of the river. In the northern parts, due to the limitation of the river on both sides, the intensity of changes is less, while in the middle parts of the river, according to the numerous constructions on both sides of the river, the intensity of destruction is also higher. One of the most important issues in using MQI method is the researcher level of expertise. Data collection is based on a combination of remote sensing, GIS analysis and field navigation and should be done by operators with background and appropriate training in river geomorphology because having specialized knowledge of river geomorphic concepts is necessary for the application of MQI.